Tramelling The Illegal Wildlife Trading: A Comparative Legislative Analysis of China and India - Sandeep Kumar Mohanty; Soumya Prakash Patra (SASI, 2021)
Illegal wildlife trade is one of the major transnational crimes. Transnational Crime, by its very nature, is problematic as it surpasses national jurisdictions, as well as the parameters of information systems and law enforcement agencies. Illegal wildlife trade networks increasingly operate like global multinational businesses, connecting local markets to the global markets through complex and interlinked networks.Against this background, CITES was entered into, multinational environmental agreement to which 183 nations are parties to it and India, being a member of CITES, in compliance with the guidelines, has enacted an umbrella of 8 legislation for the protection of wildlife in India. But despite this austere legislation, India is progressively becoming a hub of illegal wildlife trade.The illegal laundering of wild-caught animals via legal pathways is subject to increased scrutiny. It appears that illegal wildlife traders are rampantly using other covert methods to smuggle these animals into the territories of target consumer countries, such as China. Once they enter into the jurisdiction of destination countries that permit legal trade in this species, it becomes arduous for the relevant enforcement agencies to distinguish between the wild-caught and captive-bred animals.The author undertakes to carry out a comparative analysis of the existing legislation of China concerning India to understand whether the legislation is robust enough for the protection of the wildlife and how the enforcement mechanism can be strengthened for the advancement of the endangered species.